Rejoinder—Rejoinder to the Note by Yigal Gerchak - Zangwill, Willard I. (Management Science, 1988)
Gerchak's note further elaborates on an example in my paper “From EOQ Towards ZI” (Zangwill, W. I. 1987. From EOQ towards ZI. Management Sci. 33 1209–1223.). My example is correct. His example is correct also, and I was aware of examples of his type when I wrote the paper as were the referees when they reviewed it. His example makes several additional assumptions which totally change the situation and indeed the viewpoint of reality.